A case study on: penetrating Malaysia’s agricultural products into the Japanese market / Norjehan Mohamad Roff - Mohamad Roff, Norjehan (Faculty of Business and Management, 2009)
This study is conducted to examine on how Malaysia’s Agriculture Products can penetrate into the Japanese market. On this research, MATRADE and Japan has been chosen as a study setting in order to analyze on that topics. The focus of this study will be based on what is the factor that can influence and help Malaysia Agriculture products to penetrate into the Japanese Market. One of the factors is distribution channel. In contrast with the Malaysian distribution channel, the Japanese distribution channel is often characterized as a long, complicated network of relation-driven middle men who are interacting closely with “fellow-trade “wholesalers, brokers, manufacturers, importers, and retailers. Within this channel, it is not uncommon to include as many as four layers of wholesalers. Here, we can see that the Japanese distribution system is not efficient in terms of time and it involves a lot of cost. It is also inefficient for Malaysia to export agriculture products to Japan because by the time the product reaches the customer, the product will already be rotten and this will affect the quality of Malaysian agricultural products.